BANDUNG DOG SHELTER AND ADOPTION CENTER - Agung Prabawa (NIM:17313502), Gelar
In Indonesia a lot of humans and animals that are related, like many people keep animals to make their pets from animal's lover, hobbies and even as stress relievers. From lack of awareness and human responsibility of pet, lot of pets are abandoned with the worrying condition, especially inthe city of Bandung. Besides having a bad impact on the animal itself, it's going to cause some problems in the surrounding environment, especially in the form of disease - transmitted diseases from animals into humans, such as rabies. Therefore, in the city of Bandung, there needs a shelter and adoption that can accommodate and restore the character of abandoned dogs and prepare the dogs for adoption. Additionally, additional facilities such as Pet Park / Playground and Pet CafÃƒÂ© are conceptualized to be the center of information on how to properly care for dogs, to bring people closer to the animals and to tell how much of the pet benefits has to humans.